PENATALAKSANAAN PENCEGAHAN KECELAKAAN ANAK USIA PRASEKOLAH DI DUSUN GEBLAGAN KECAMATAN KASIHAN KABUPATEN BANTUL - Aji Satria Nugratmaja (PSIK 11 UMY, 2011)
Ages birth to school age are a golden period, which is determine the further development of the children. This period is an appropriate time to preserve the basics development of physical ability, language, social, emotional, self-concept, art, morals and religious values. While preschool age, children will be more frequently injured and it could affect the process of further developments. This research purpose is to knowing the management of accident prevention in preschoolers in Geblagan Haml